2012
DOI: 10.1007/s11205-012-0114-9
|View full text |Cite
|
Sign up to set email alerts
|

Why is Housing Always Satisfactory? A Study into the Impact of Preference and Experience on Housing Appreciation

Abstract: This study focuses on residents’ perceptions of residential quality concerning 23 different dwelling aspects. Respondents were asked to indicate their appreciation of these dwelling aspects on a scale ranging from 0 (“extremely unattractive”) to 100 (“extremely attractive”). The influence of two potential factors on the appreciation of dwelling aspects is examined: (1) preference and (2) experience. It was hypothesized that residents who live according to their preferences give higher appreciation scores than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 28 publications
(45 reference statements)
2
27
0
1
Order By: Relevance
“…The findings concur with those of previous studies , which showed that satisfaction with housing was closely associated with the physical environment. Furthermore, it is noteworthy that these aspects are similarly important and universally applicable for people in general . Thus, where environmental or physical aspects of the housing situation for this group are concerned, nursing staff and planners should not necessarily need to think in terms of special needs demanding special solutions but rather to reflect on the question ‘what are the best solutions?’ By considering this answer together with the response from the target group themselves, should provide sufficient guidance for nursing staff in their work to help and support people with psychiatric disabilities in improving their housing situation.…”
Section: Discussionmentioning
confidence: 99%
“…The findings concur with those of previous studies , which showed that satisfaction with housing was closely associated with the physical environment. Furthermore, it is noteworthy that these aspects are similarly important and universally applicable for people in general . Thus, where environmental or physical aspects of the housing situation for this group are concerned, nursing staff and planners should not necessarily need to think in terms of special needs demanding special solutions but rather to reflect on the question ‘what are the best solutions?’ By considering this answer together with the response from the target group themselves, should provide sufficient guidance for nursing staff in their work to help and support people with psychiatric disabilities in improving their housing situation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies find that residential satisfaction has small variations among residents living in different neighborhoods (McCrea et al, 2014;McCrea et al, 2005) and that residents are satisfied even when they live in poor conditions (Amérigo and Aragonés, 1990;Amos et al, 1982;Jansen, 2013). They argue that residents choose residential places that meet their needs (or preferences) the best and hence are satisfied (Amérigo and Aragonés, 1997;McCrea et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction with housing has also been shown in other populations to be influenced by underlying factors. For example, Jansen (2013) maintains, in a study of the general population, that there is a tendency for people to be satisfied with the housing situation they already have, due to them being used to it, even if it does not concur with their preferences.…”
mentioning
confidence: 99%